HARTA BERSAMA DALAM PERKAWINAN - Faizal, Liky (Universitas Islam Negeri Raden Intan Lampung, 2015)
A legal act that is causing the joint property is marriage,whether marriage is governed by article 26 KUHPdt andso on, as well as marriage as stipulated in UU No. 1/1974about marriage. Breakup of marriage either through deathor divorce (divorce to sue or divorce divorce), oftencause a secondary effect that is often not resolved well,aside from the determination of the status of childcustody, subsistence, also on the division of jointproperty, which is also often a trigger the new conflictbetween husband and wife after the divorce. How the lawof community property in a marriage based approachIslamic law and positive law of Indonesia became a staplein the study of this article.